Research and Simulation of the Kinematics of Dual-arm 6R Service Robot - Li Xianhua; Sun Qing; Zhang Leigang; Zhang Jun (Jixie chuandong)
Aiming at the inverse solution problem of the kinematics of dual-arm service robot,a inverse kinematics solution is proposed according to its configuration characteristics. Firstly,according to the structure characteristics of the manipulator,the forward kinematics model of dual-arm is got by using the method of standard DH modeling. A group of completely generalized coordinates is obtained by inverse transformation method of manipulator posture matrix using Euler angles. Then,the inverse kinematics of dual-arm6 R robot is solved by geometrical method and coordinate projection method. After analysis and calculation,the closed solutions of 8 groups can be obtained,and the optimal solution is selected. Finally,a 3 D simulation platform is established to verify the correctness of inverse kinematics based on MATLAB,and it lays the foundation for the trajectory planning and collision avoidance of manipulator.